Breaking the Barriers: Flash Card Media’s Role in Enhanching Literacy for Students with Special Needs - Zumrotul Mukaffa; Uswatun Chasanah; Majidatun Ahmala (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research is motivated by the phenomenon of the low literacy culture of the Indonesian people, which, according to UNESCO, are ranked 60th out of 61 countries. In a year, children in Europe and America can read about 25-27% of books, children in Japan are around 15-18%, while Indonesian children only reach 0.01%. The phenomenon of low interest in reading books also occurs in students with special needs at a private Elementary School. This study aims to improve the literacy skills of students with special needs at an elementary school using flash card media. This study uses an experimental approach, with a pre-experimental model carried out by (pretest-posttest design). The group observed was ten students with special needs in low grades with down syndrome, speech delay, meningitis, slow learning, and dyslexia. The results showed that the flash card media improved the literacy skills (reading at the beginning) of students with special needs with a significance value of 0.007 0.05, which means that the statistical test significance of reading skills scores is smaller than the significance limit value. The improvement of literacy skills (reading the beginning) is also influenced by attractive, illustrated and colourful flash card media design. This results in students being more interested in learning to read and more accessible to understanding the studied concepts.